Manifestasi Teori Komunikasi Sosial dalam Kampanye Sedekah Sampah untuk Mengatasi Krisis Iklim di Wilayah Pesisir Lombok Barat - Muhamad Khalid Iswadi; Idham Halid; Pauzan; Alfan Hadi (Jurnal Pengabdian Kepada Masyarakat Al-Amin, 2025)
Waste management, especially plastic waste, poses a significant challenge in addressing the climate crisis in coastal areas. This study aims to apply a participatory approach that integrates the principles of social communication and the community-based behavior change theory (Community-Based Social Marketing, CBSM) in the sedekah sampah (waste charity) campaign in Sekotong Barat Village, specifically in Dusun Medang and the Cemara Beach area. The method used is social communication to raise community awareness about the importance of waste management, followed by an invitation for active participation in the sedekah sampah movement, which involves valuable waste. The campaign is driven by the CBSM model, which has proven effective in changing community behavior toward environmental issues. This model engages the community directly in planning and implementing waste reduction programs. The results of this community service indicate an increase in participation, and plastic waste, which was previously considered trash, is now viewed as a valuable resource for social purposes. This approach also successfully transformed community behavior in waste management in the coastal area, creating awareness and tangible actions in reducing plastic waste.